Pengaruh Disiplin Kerja terhadap Kinerja Karyawan di PT BPR Hayura Artalola Kabupaten Bandung - Ricky Herdiana; Alda Ramadhika (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to determine the effect of work discipline on employee performance at PT BPR Hayura Artalola. The research method used is a quantitative research method with a descriptive and verificative approach. The sample in this study was a total sample with 30 respondents. To answer the research questions, SPSS version 25 was used. The results of the determination test of work discipline on employee performance were 0.674, indicating that work discipline had a 67.4% influence on performance. The results of the regression test of work discipline on employee performance had a positive direction coefficient of 0.850. The results of the correlation test of work discipline on employee performance had a value of 0.821 or 82.1%, which means that there is a very strong positive correlation between work discipline and employee performance. The results showed that work discipline had a positive and significant effect on employee performance. Work discipline can explain 67.4% of the variation in employee performance, with a correlation of 82.1%, which indicates a very strong relationship. As a result, improving work discipline can directly increase effectiveness, responsibility, and productivity related to employee performance. Therefore, strengthening a culture of work discipline is an important strategy for improving performance at PT BPR Hayura Artalola.